Advanced Virological And Clinicopathological Studies On Cattle Suffering From Foot And Mouth Disease Virus - Ahmed Kamal Samia; Abd El-Rahman Hassan Randa (Journal of Immunization, 2017)
Some strains of Foot and mouth disease virus (FMDV) are endemic in Egypt. The present study was performed on cattle and buffaloes (ages: 3 months up to 1.5 years old, of years 2015 and 2016), which were suffering foot and mouth disease (FMD). Sera and tissues samples were tested by different techniques including serum and virus neutralization tests (SNT, VNT), virus isolation and identification by tissue culture methods, Enzyme linked immune-Sorbent Assays (ELISA); and by the pathological and hematology techniques. The results showed the predominance of FMDV serotype O with the presence of serotypes SAT2 and A. The results showed the pathologic picture of FMD was similar regardless its specific subtypes, as apparently the studied strains produces same pathological and hematological changes. Microscopic examination reveals severe hydropic degenerations and necrosis in most affected organs, accompanied by significant changes in blood parameters which indicate severity and direct effects of FMDV on the hematopoietic system. These findings indicates the mode of pathogenesis of FMD virus in its way to exhibits the characteristic symptoms of illness. However, the investigation showed the presence of FMDV type O, A and SAT2 in the studied areas of delta governorates. It is important to focus on producing of vaccines which have only these serotypes as solution to get rid of the endemic behavior of FMDV in delta of Egypt.
Keywords: FMDV